PATIENT LOYALTY :THE INFLUENCE OF WORD MOUTH AND SERVICE QUALITY - Asia, Sri; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Patient loyalty is a very valuable asset for any hospital because it can generate positive recommendations to others and build a good reputation in the community. This research aims to analyze the influence of Word of Mouth (WOM), service quality, and patient loyalty at Bhayangkara Hospital Kendari. The respondents in this study were 117 patients. The data analysis method used was Partial Least Square (PLS). This study emphasizes that positive word-of-mouth recommendations (WOM) and perceptions of service quality play a crucial role in influencing the level of patient loyalty towards a healthcare facility. The research findings indicate that WOM leading to positive recommendations, along with positive experiences with service quality, have a significant impact on patient loyalty. The implications of this study emphasize the importance of paying attention to and enhancing WOM, as well as ensuring patient satisfaction and trust in the quality of services provided, as crucial strategies for maintaining and increasing patient loyalty in the healthcare sector. Keywords: Word Of Mouth, Service Quality, Patient Loyalty.